Monitoring Temporal Urban Expansion and Its Effect on LST Using Landsat Imagery (OODBODHAN, 2026)
Nepal is one of the fastest urbanizing nations in South East Asia. Nepal’s terai region has been facing huge pressure of urbanization due to rising population and rapid migration of people from hilly region to flat low lands. Bharatpur metropolitan city lies in Chitwan Nepal. The fertile lands of Bharatpur has been depleted to adjust the growing urban areas. This study assess the physical expansion of urban areas in Bharatpur Metropolitan City using Landsat imageries from years 2000, 2010 and 2020 and its effect on Land Surface Temperature. The Land Use/ Land Cover map revealed that there was massive increase of the built up area in the region in the period of 20 years. The built up area increased from 1.53 km2 in 2000 to 30.02 km2 in 2020. It has outgrown from urban core to extremity of the metropolitan city. By integrating temporal Land Use Land Cover (LULC) data with Shannon’s Entropy, it is confirmed that the expansion of the built up area is highly disorganized. The Relative Shannon’s Entropy value has rose from 0.56 to 0.88 in 2020, categorizing expansion of Bharatpur as “Extreme Sprawl”. Built up areas consistently recorded the highest mean temperature across all three temporal periods. The conversion of natural land into heat retaining impervious surface has significantly changed the thermal pattern of the city.